Hydrolysis of VX on Concrete: Rate of Degradation by Direct Surface Interrogation Using an Ion Trap Secondary Ion Mass Spectrometer - Groenewold, Gary S; Williams, John M; Appelhans, Anthony D; Gresham, Garold L; Olson, John E; Jeffery, Mark T; Rowland, Brad (Environmental science & technology, 2002)
The nerve agent VX (O-ethyl S-2-diisopropylaminoethyl methylphosphonothiolate) is lethal at very low levels of exposure, which can occur by dermal contact with contaminated surfaces. Hence, behavior of VX in contact with common urban or industrial surfaces is a subject of acute interest. In the present study, VX was found to undergo complete degradation when in contact with concrete surfaces. The degradation was directly interrogated at submonolayer concentrations by periodically performing secondary ion mass spectrometry (SIMS) analyses after exposure of the concrete to VX. The abundance of the [VX + H]+ ion in the SIMS spectra was observed to decrease in an exponential fashion, consistent with first-order or pseudo-first-order behavior. This phenomenon enabled the rate constant to be determined at 0.005 min-1 at 25 °C, which corresponds to a half-life of about 3 h on the concrete surface. The decrease in [VX + H]+ was accompanied by an increase in the abundance of the principal degradation product diisopropylaminoethanethiol (DESH), which arises by cleavage of the P−S bond. Degradation to form DESH is accompanied by the formation of ethyl methylphosphonic acid, which is observable only in the negative ion spectrum. A second degradation product was also implicated, which corresponded to a diisopropylvinylamine isomer (perhaps N,N-diisopropyl aziridinium) that arose via cleavage of the S−C bond. No evidence was observed for the formation of the toxic S-2-diisopropylaminoethyl methylphosphonothioic acid. The degradation rate constants were measured at four different temperatures (24−50 °C), which resulted in a linear Arrhenius relationship and an activation energy of 52 kJ mol-1. This value agrees with previous values observed for VX hydrolysis in alkaline solutions, which suggests that the degradation of submonolayer VX is dominated by alkaline hydrolysis within the adventitious water film on the concrete surface.